The Effectiveness of the KPU Goes To Campus and Goes To School Programs in Increasing Voter Participation in the 2024 South Sumatra Regional Elections - Rhiezka Amelia Pratiwi; Dwiki Adi Putra; Isabella (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This study aims to determine the Effectiveness of the Services of the South Sumatra Provincial General Election Commission in providing information about the South Sumatra Simultaneous Regional Elections. In this study, the researcher uses a Qualitative Method where the researcher gets an appropriate and targeted data through interviews, observations and documentation. The results of this study show that by using the theory that has been analyzed, namely the Theory of Effectiveness which has 4 indicators, namely (1) Accuracy of Program Targets, (2) Program Socialization, (3) Program Objectives and (4) Program Monitoring which has fulfilled the basis as a design for the Service Effectiveness of the South Sumatra Provincial General Election Commission in providing information about the South Sumatra Simultaneous Regional Elections. Then the results of the analysis and findings in the field from this study show that the South Sumatra Provincial General Election Commission has shown significant progress in providing information related to the Simultaneous Regional Elections. However, there is still room for improvement, especially in terms of access to information for remote areas and the expansion of the reach of socialization. It can be concluded that currently the effectiveness of the South Sumatra Provincial General Election Commission in providing information about the South Sumatra Simultaneous Regional Elections still needs to be improved. In the future, the effectiveness of the service needs to be focused on expanding the reach of socialization to remote areas.